Towards a turquoise organization – personal change of employees and its socio-cultural barriers - Tabaszewska-Zajbert, Edyta; Sokołowska-Durkalec, Agnieszka (W kierunku turkusowej organizacji – zmiana osobista pracowników i jej bariery społeczno-kulturowe, 2019)
A turquoise organization is one of the new organization models, created in the course of research by the Belgian business practitioner F. Laloux. The basic assumptions for the functioning of this organization, otherwise known as a teal organization, are a sense of mission, wholeness of humanity and self-management. The aim of the study is to indicate the personal development of employees as the main condition for transformation into a turquoise organization. In addition, the basic social and cultural barriers of the expected personal change were pointed out, with particular emphasis on Polish conditions. The basic barriers include, first of all, a low level of social trust together with unacceptable openness in expressing emotions, a faulty educational system, and barriers related to organizational culture. The study was based on literature studies and the presentation of the results of selected foreign empirical studies
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 9, s. 200-210
Keywords: turquoise organization; teal organization; personal change; personal development; socio-cultural barriers; organizacja turkusowa; żywa organizacja; zmiana osobista; rozwój osobisty; bariery społeczno-kulturowe